Theory of Modeling and Simulation : Discrete Event & Iterative System Computational Foundations /: Discrete Event & Iterative System Computational Foundations. (2018) - Zeigler, Bernard P; Muzy, Alexandre; Kofman, Ernesto
No abstract available